THE EFFECT OF THE USE OF THE DURUS AL-LUGAH AL-’ARABIYYAH ’ALA AL-TARIQAH AL-HADISAH BOOK ON LANGUAGE SKILLS AT DARUL HUFFADH TUJU-TUJU ISLAMIC BOARDING SCHOOL KAJUARA BONE
This study aims to analyze whether there is an effect of using the book of Durus al-Lugah al-’Arabiyyah ’ala al-Tariqah al-Hadisah on language skills. It investigated the students in the first grade at Darul Huffadh Tuju-tuju Islamic Boarding School Kajuara Bone. This study was a quantitative research with an Expost Facto approach by collecting and simplifying the data collected using the SPSS application in processing the data. There were two variables in this study, namely the use of the Durus al-Lugah book as a variable (X) and language skills as a variable (Y). While the population in this study was 299 students of KMI in the first grade and the sample was 20% of the population, namely 60 students. The data collection method used questionnaires, tests, documentation and observation. The data analysis used descriptive and inferential statistical analysis. The study results indicate that (1) The use of the Durus al-Lugah al-’Arabiyyah ’alaal-T